2022
DOI: 10.1088/1367-2630/ac5aef
|View full text |Cite
|
Sign up to set email alerts
|

Multifrequency Bessel beams with adjustable group velocity and longitudinal acceleration in free space

Abstract: The group velocity of an optical beam in free space is usually considered to be equal to the speed of light in vacuum. However, it has been recently realized that, by structuring the beam's angular and temporal spectra, one can achieve well pronounced and controlled subluminal and superluminal propagation. In this work, we consider multifrequency Bessel beams that are known to propagate without divergence and show a variety of possibilities to adjust the group velocity of the beam by means of designed angular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Measured group velocity of the longitudinally accelerating Bessel beam (see the blue dots and the estimated error bars).The blue line shows the theoretically predicted group velocity of the beam. The curve corresponds to the theoretical curve shown in Fig.6of Ref [21]. for the current parameter values.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Measured group velocity of the longitudinally accelerating Bessel beam (see the blue dots and the estimated error bars).The blue line shows the theoretically predicted group velocity of the beam. The curve corresponds to the theoretical curve shown in Fig.6of Ref [21]. for the current parameter values.…”
mentioning
confidence: 74%
“…Recently, a systematic theoretical description of structured pulsed and cw laser beams with varying group velocities in free space has been presented [21]. There it was shown that, for cw beams, the velocity of the intensity peaks can fluctuate or change deterministically both in space and time.…”
mentioning
confidence: 99%
See 1 more Smart Citation